2016
DOI: 10.1016/j.clinthera.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Gastrointestinal and Respiratory Microbiome in Cystic Fibrosis: Potential Interactions and Implications for Systemic Health

Abstract: Purpose The gastrointestinal microbiome plays a critical role in nutrition and metabolic and immune functions in infants and young children and has implications for lifelong health. Cystic fibrosis (CF) transmembrane conductance regulator (CFTR) mutations in CF result in viscous mucous production, frequent exposure to antibiotics, and atypical colonization patterns, resulting in an evolving dysbiosis of the gastrointestinal and respiratory microsystems; dysbiosis in CF results in systemic inflammation, chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
(67 reference statements)
1
20
0
1
Order By: Relevance
“…In fact, the corresponding absolute abundance of P. aeruginosa was still higher in murine lungs treated with PA14 in 2,3-butanediol even with the increased colonization of environmental microbes (Supplementary Figure S3C). Our results are also consistent with the recent studies that have shown the impact of gut microbiome on acquisition of the lung microbiome in CF (Madan, 2016).…”
supporting
confidence: 93%
“…In fact, the corresponding absolute abundance of P. aeruginosa was still higher in murine lungs treated with PA14 in 2,3-butanediol even with the increased colonization of environmental microbes (Supplementary Figure S3C). Our results are also consistent with the recent studies that have shown the impact of gut microbiome on acquisition of the lung microbiome in CF (Madan, 2016).…”
supporting
confidence: 93%
“…Indeed, it has been demonstrated that neutrophil biogenesis and aging in mice is controlled, in part, by the gut microbiome [39, 40]. In patients with chronic infections, e.g., CF or COPD, it is likely that the lung microbiome could also play a role in shaping neutrophil lifespan [41], although this notion remains controversial [42, 43]. …”
Section: Reviewmentioning
confidence: 99%
“…In turn, the GI physicochemical environment, which is decidedly altered in people with CF, shapes both the constituency and behavior of the GI microbiota. Recent evidence shows that CF GI microbiota are indeed different from people without CF, potentially with pathological consequences within and beyond the CF GI tract . In this article, we will review the recent literature on the CF GI microbiome and its clinical impact, as well as how we might use these recent discoveries to prevent a host of CF disease manifestations.…”
Section: Introductionmentioning
confidence: 99%